Last updated at Dec. 16, 2024 by Teachoo
Ex 8.3, 5 (c) Subtract: 3l (l – 4 m + 5 n) from 4l (10 n – 3 m + 2 l)3l (l – 4m + 5n) = (3l × l) + (3l × –4m) + (3l × 5n) = 3l2 – 12lm + 15ln 4l (10 n – 3 m + 2 l) = (4l × 10n) + (4l × –3m) + (4l × 2l) = 40ln – 12lm + 8l2 = 8l2 – 12lm + 40ln Simplifying expressions We have to subtract 1st expression from the 2nd expression. So, we write 2nd expression first. Putting like terms below like terms. So, our answer is 5l2 + 25 ln
About the Author
Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 14 years. He provides courses for Maths, Science and Computer Science at Teachoo